Severity of Cardiovascular Disease Outcomes Among Patients With HIV Is Related to Markers of Inflammation and Coagulation. Issue 3 (28th May 2014) - Nordell, Anna D.; McKenna, Matthew; Borges, Álvaro H.; Duprez, Daniel; Neuhaus, Jacqueline; Neaton, James D.; ,
Abstract : Background: In the general population, raised levels of inflammatory markers are stronger predictors of fatal than nonfatal cardiovascular disease (CVD) events. People with HIV have elevated levels of interleukin‐6 (IL‐6), high‐sensitivity C‐reactive protein (hsCRP), and D‐dimer; HIV‐induced activation of inflammatory and coagulation pathways may be responsible for their greater risk of CVD. Whether the enhanced inflammation and coagulation associated with HIV is associated with more fatal CVD events has not been investigated. Methods and Results: Biomarkers were measured at baseline for 9764 patients with HIV and no history of CVD. Of these patients, we focus on the 288 that experienced either a fatal (n=74) or nonfatal (n=214) CVD event over a median of 5 years. Odds ratios (ORs) (fatal versus nonfatal CVD) (95% confidence intervals [CIs]) associated with a doubling of IL‐6, D‐dimer, hsCRP, and a 1‐unit increase in an IL‐6 and D‐dimer score, measured a median of 2.6 years before the event, were 1.39 (1.07 to 1.79), 1.40 (1.10 to 1.78), 1.09 (0.93 to 1.28), and 1.51 (1.15 to 1.97), respectively. Of the 214 patients with nonfatal CVD, 23 died during follow‐up. Hazard ratios (95% CI) for all‐cause mortality were 1.72 (1.28 to 2.31), 1.73 (1.27 to 2.36), 1.44 (1.15 to 1.80), and 1.88 (1.39 to 2.55), respectively, for IL‐6, D‐dimer, hsCRP, and the IL‐6 and D‐dimer score. Conclusions: Higher IL‐6 and D‐dimer levels reflecting enhanced inflammation and coagulation associated with HIV are associated with a greater risk of fatal CVD and a greater risk of death after a nonfatal CVD event. Clinical Trial Registration: URL:http://www.clinicaltrial.gov Unique identifier: SMART: NCT00027352, ESPRIT: NCT00004978, SILCAAT: NCT00013611.